ANALISIS KEPUASAN NASABAH DENGAN PENDEKATAN FUZZY SERVICE QUALITY DALAM UPAYA PENINGKATAN KUALITAS LAYANAN PERBANKAN (Studi Kasus di Bank Mandiri Cabang Sudirman Yogyakarta) - Abdul Djalal (Faculty of Industrial Technology Universitas Islam Indonesia, 2013)
Servqual Dimension in gap measuring is used over recovering program in controlling service as the alternatives for the service quality improving towards customer satisfaction, as one of the company strategy to empower Total Quality Service. Measuring the service quality using servqual is the other way to discover customer satisfaction over service quality employs in PT. Bank Mandiri (Persero) Tbk Sudirman Branch. Hence, it could be further measured the gap between customer perception with their expectation by placing it in service dimension: Reliability, Response, Assurance, Empathy. Questionnaire test using Likert scale is employed to obtain physical evidence of measurement. Furthermore, 75 questionnaires of 80 are collected. Later, data is processed using Fuzzy-Servqual Method. Information for average gap of each dimension finally concluded as follow: Response (-0,158), Emphaty (0,05), physical evidence (0,176), Reliability (0,291) and Assurance (0,514). It shown that, overall the service quality at PT. Bank Mandiri (Persero) Tbk Sudirman Branch considered as good. It can be said that its service quality is accommodate every customer necessities